FEMA GRAS assessment of natural flavor complexes: Origanum oil, thyme oil and related phenol derivative-containing flavoring ingredients. (September 2021) - Cohen, Samuel M.; Eisenbrand, Gerhard; Fukushima, Shoji; Gooderham, Nigel J.; Guengerich, F. Peter; Hecht, Stephen S.; Rietjens, Ivonne M.C.M.; Rosol, Thomas J.; Davidsen, Jeanne M.; Harman, Christie L.; Lu, Vivian; Taylor, Sean V.
Abstract: In 2015, the Expert Panel of the Flavor and Extract Manufacturers Association (FEMA) initiated a re-evaluation of the safety of over 250 natural flavor complexes (NFCs) used as flavor ingredients, mostly consisting of a variety of essential oils and botanical extracts. This publication, seventh in the series, re-evaluates NFCs with constituent profiles dominated by phenolic derivatives including carvacrol, thymol and related compounds using a constituent-based procedure first published in 2005 and updated in 2018. The procedure is based on the chemical characterization of each NFC as intended for commerce and the estimated intake of the constituent congeneric groups. The procedure applies the threshold of toxicological concern (TTC) concept and evaluates relevant data on absorption, metabolism, genotoxic potential and toxicology of the constituent congeneric groups and the NFC under evaluation. Herein, the FEMA Expert Panel affirmed the generally recognized as safe (GRAS) status of seven phenolic derivative-based NFCs, Origanum Oil (Extractive) (FEMA 2828), Savory Summer Oil (FEMA 3013), Savory Summer Oleoresin (FEMA 3014), Savory Winter Oil (FEMA 3016), Savory Winter Oleoresin (FEMA 3017), Thyme Oil (FEMA 3064) and Thyme White Oil (FEMA 3065) under their conditions of intended use as flavor ingredients. Highlights: Safety evaluation of natural flavoring ingredients containing phenolic constituents. Evaluation used procedure developed by the FEMA Expert Panel for natural flavors. FEMA GRAS status affirmed for 7 natural flavor complexes.